Discovery of a conserved Plasmodium antigen on the surface of malaria-infected red blood cells - Oteng, EK (2013)
During its intraerythrocytic stages (IE), Plasmodium falciparum, the causative agent of the deadliest human malaria, remodels the host red cell membrane with a poorly defined assortment of parasite-encoded proteins that undergo antigenic variation. Despite the requirement for immunologic stealth, exported parasite proteins also mediate strain-independent functions such as endothelial sequestration that are critical for parasite survival and pathogenesis. This thesis explores the hypothesis that P. falciparum displays novel structurally conserved proteins on the IE surface and these proteins may serve as useful antigens for a broadly effective anti-malarial vaccine. In order to test this hypothesis, we developed an in vitro selection technique that sequentially incorporates unique P. falciparum isolates as the targets for Systematic Evolution of Ligands by EXponential enrichment (Serial-SELEX) to generate nucleic acid molecular probes, aptamers, capable of recognizing conserved cell surface determinants. Ten of 11 enriched aptamers were -parasite selective and three of these aptamers demonstrated strain-independent binding to P. falciparum. Aptamer recognition extended beyond the parasites used in Serial-SELEX to other laboratory and recent field isolates. Surprisingly the same three broadly binding aptamer selected against P. falciparum also recognized all laboratory-adapted and clinical isolates of P. vivax and P. knowlesi tested, strongly supporting our hypothesis that structurally conserved molecules are present on the surface IEs. Competition studies showed that the aptamers bound a single target which was confirmed as an IE membrane protein. Aptamer‐mediated affinity purification and tandem mass spectrometry enabled identification of the aptamer target as parasite-encoded protein. Discovery of a protein conserved between the major human malarias may have implications for vaccine development and validates the Serial‑SELEX technique as a powerful tool for antigen discovery.